2015
DOI: 10.3945/jn.114.203158
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Hepcidin Is Part of a Complex Relation That Links Mortality with Iron Homeostasis and Anemia in Men and Women with HIV Infection

Abstract: Background: Early and chronic inflammation is a hallmark of HIV infection, and inflammation is known to increase hepcidin expression. Consequently, hepcidin may be a key determinant of the iron homeostasis and anemia associated with poorer HIV prognoses. Objective: The objective of this study was to understand how hepcidin is related to anemia, iron homeostasis, and inflammation at HIV diagnosis and to investigate associations between hepcidin and all-cause mortality in HIV infection. Methods: In a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The authors attempted to correct for the impact of HIV infection by adjusting the results based on C‐reactive protein (CRP) levels. HIV infection is an independent contributor to iron deficiency (Minchella et al ., ). The effect of HIV status of included women in the study by van den Broek et al .…”
Section: Discussionmentioning
confidence: 97%
“…The authors attempted to correct for the impact of HIV infection by adjusting the results based on C‐reactive protein (CRP) levels. HIV infection is an independent contributor to iron deficiency (Minchella et al ., ). The effect of HIV status of included women in the study by van den Broek et al .…”
Section: Discussionmentioning
confidence: 97%
“…HIV/AIDS, similarly to other chronic infections, has been reported to lead to immune-mediated anemia of chronic disease, iron deficiency anemia or their combination (Kerkhoff and Lawn, 2015;Minchella et al, 2015), in which differential expression of hepcidin, hemojuvelin, ferroportin and other factors plays an important role (Drakesmith and Prentice, 2012;Krijt et al, 2004;Theurl et al, 2011;Xu et al, 2010). Consequently, iron supplements have often been administered.…”
Section: Discussionmentioning
confidence: 99%
“…Following the first studies showing a Toll-like receptor (TLR) 4-dependent induction of hepcidin by LPS, in vivo mouse studies showed increased levels of hepcidin during infections with Salmonella [ 35 , 36 ], Pseudomonas aeruginosa , group A Streptococcus [ 37 ], Vibrio vulnificus [ 38 ], and Candida albicans or Influenza A virus [ 39 ]. Additionally, in humans, several types of infections, including HIV, Salmonella , tuberculosis, sepsis, and malaria, have been reported to be accompanied by increased levels of serum hepcidin [ 40 , 41 , 42 , 43 , 44 ]. In marked contrast, the Hepatitis C virus inhibits hepcidin production in humans, which contributes to the pathology of this disease [ 45 ].…”
Section: Different Pathogens Different Impacts On the Iron Metabomentioning
confidence: 99%